Model-independent test of the cosmic anisotropy with inverse distance ladder - Zong-Fan Yang; Da-Wei Yao; M. Le Delliou; Ke Wang (European Physical Journal C: Particles and Fields)
Abstract If the Universe is endowed with cosmic anisotropy, it will have a preferred direction of expansion. By reconstructing the expansion history using a Gaussian process (GP), researchers can probe the cosmic anisotropy model-independently. In this paper, for the luminosity distance $$d_L(z)$$ d L ( z ) reconstruction, we turn to the inverse distance ladder, where type Ia supernovae (SNIa) from the Pantheon+ sample determine relative distances, and strongly gravitationally lensed quasars from the H0LiCOW sample anchor these relative distances with some absolute distance measurements. By isolating the anisotropic information that could be carried by the Hubble constant $$H_0$$ H 0 and obtaining constraints on the intrinsic parameter of SNIa, the absolute magnitude $$M=-19.2522^{+0.0594}_{-0.0649}$$ M = - 19 . 2522 - 0.0649 + 0.0594 (at $$68%$$ 68 % CL), we find that $$d_L(z)$$ d L ( z ) reconstructions from samples located in different regions of the galactic coordinate system are almost consistent with each other, while only a very weak preference for the cosmic anisotropy is found.